PEMBERDAYAAN MASYARAKAT LOKAL DALAM PENGOLAHAN TRADISIONAL MINYAK BUAH MERAH DI KAMPUNG SEGIOR DISTRIK AYAMARU JAYA KABUPATEN MAYBRAT - Maruapey, Azis; Kamaluddin, Kamaluddin; Nanlohy, Lona H.; Wahid, Bustamin; Lestaluhu, Rajab; Hahury, Sanny; Saeni, Fajrianto (Yayasan Education and Social Center, 2025)
The aim of this service is to empower the community in processing red fruit oil in the local community in Segior Village, Ayamaru Jaya District, Maybrat Regency. Actions carried out to awaken the mindset, creativity and entrepreneurial spirit of local communities through empowerment actions in processing red fruit oil so that it has economic value for local households. This activity was carried out collaboratively and synergistically between the local community and UM Sorong lecturers. The method used in Empowering Local Communities in Processing Red Fruit Oil through community empowerment carried out in the form of Collaborative Action activities with a persuasive and andragogical approach model. The results of this community service activity have identified how to build understanding (mindset) and creative power of local communities in processing red fruit oil and opening up market information. This empowerment is also the main foundation for strengthening and developing red fruit oil processing businesses.